The Minkowski’s inequality by means of a generalized fractional integral - J. Vanterler da C. Sousa; E. Capelas de Oliveira (AIMS Mathematics, 2018)
We use the definition of a fractional integral, recently proposed by Katugampola, to establisha generalization of the reverse Minkowski’s inequality. We show two new theorems associatedwith this inequality, as well as state and show other inequalities related to this fractional operator.